PUBLIC SERVICE MANAGEMENT IN ARCHIPELAGIC REGIONS: A SYSTEMATIC LITERATURE REVIEW - Sakir, Ahmad Rosandi (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2025)
This study explores public service management in archipelagic regions through a systematic literature review of research published over the last five years. Archipelagic regions present unique challenges due to geographical isolation, limited resources, and infrastructure disparities, which directly affect the accessibility and effectiveness of public services. By synthesizing findings from five key studies, including empirical case studies and policy reports, this review highlights four critical themes: geography-based governance, alternative governance arrangements in resource-deficient contexts, community participation, and digital transformation. The analysis reveals that geography plays a central role in shaping governance models, requiring adaptive and decentralized approaches that acknowledge the realities of small island contexts. Furthermore, innovative governance structures are necessary when resources are scarce, with community-based and multi-actor collaboration emerging as viable strategies. Public participation also proves essential in enhancing trust, legitimacy, and sustainability of services, particularly in small island nations. At the same time, digitalization offers significant opportunities for bridging service gaps, but infrastructure inequalities remain a major obstacle. This review concludes that effective public service management in archipelagic regions requires a hybrid model that combines geographic sensitivity, participatory practices, and digital innovation. Nevertheless, the study is limited by its reliance on secondary literature and the absence of primary field data. Future research should include empirical investigations to provide more operational insights into policy and practice tailored for diverse island communities.